2022
DOI: 10.34067/kid.0004772022
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Citrate Is Associated with Kidney Outcomes in Early Polycystic Kidney Disease

Abstract: This is an Early Access article. Please select the PDF button, above, to view it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…This would be expected to have implications for cellular metabolism in cells expressing SLC13A5, with the higher circulating plasma citrate levels also potentially impacting metabolism systemically. Consistent with the results of our main genetic analyses, previous work has identified protective effects of citrate in various animal models of kidney disease [1,6,55,56]. Although the main IVW Mendelian randomization analysis investigating effects of plasma citrate levels did not identify evidence supporting effects on parameters of kidney function, there was strong evidence of heterogeneity in estimates generated by individual SNPs, consistent with the presence of pleiotropic effects that could bias the main IVW analyses [43].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This would be expected to have implications for cellular metabolism in cells expressing SLC13A5, with the higher circulating plasma citrate levels also potentially impacting metabolism systemically. Consistent with the results of our main genetic analyses, previous work has identified protective effects of citrate in various animal models of kidney disease [1,6,55,56]. Although the main IVW Mendelian randomization analysis investigating effects of plasma citrate levels did not identify evidence supporting effects on parameters of kidney function, there was strong evidence of heterogeneity in estimates generated by individual SNPs, consistent with the presence of pleiotropic effects that could bias the main IVW analyses [43].…”
Section: Discussionsupporting
confidence: 88%
“…This would be in-keeping with the favourable effects of SLC13A5 on kidney function occurring through its effects on plasma citrate. It has been reported that low citrate levels in urine are associated with various forms of kidney disease, and low urinary citrate is a biomarker for kidney disease progression [55,[57][58][59][60][61][62]. Furthermore, pre-clinical studies with SLC13A5 knockout mice have supported effects on sympathoadrenal mechanisms [63], which may also contribute to nephroprotective effects of genetically proxied SLC13A5 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In ADPKD, there is an interesting link among crystal formation, citrate, and disease progression, which further underlines the importance of this point. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…24,25 Conversely, there is evidence that kidney stone formation accelerates cyst growth, and hypocitraturia is associated with faster eGFR decline. 26,27 Some studies have shown that patients with kidney stones are at risk of exceeding safe levels of radiation. 18 Like ADPKD, the diagnosis and management of kidney stones relies heavily on imaging techniques, specifically CT scans.…”
Section: Discussionmentioning
confidence: 99%